The status quo of enterprise architecture implementation in South African financial services companies - M. C. Matthee; P. K.J. Tobin; P. Van Der Merwe (South African Journal of Business Management, 2007)
This article presents the findings of research that was conducted amongst Enterprise Architecture (EA) practitioners in the South African financial services sector. Due to the duration and cost implications of EA projects, factors that contribute to the success and failure of EA initiatives need to be investigated and identified. The research was largely based on a similar international study that was conducted by Schekkerman (2004b). A number of aspects of EA were investigated, including the place of EA in organisational and strategic governance, the EA architects, practices and processes, as well as the measurement of EA initiatives. Key findings from the study were that South African companies surveyed demonstrated lower levels of maturity in their approaches to the management of EA practices and processes; also identified were significant differences in the approach in South African respondents compared to international studies with respect to ownership of EA initiatives and the types of EA frameworks and modelling techniques in use.
Keywords: 650